THE USE OF PHOTOGRAPHS ON INSTAGRAM IN TEACHING DESCRIPTIVE TEXT TO IMPROVE STUDENTS’ WRITING SKILL - Purwandari, Mustika (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
This research was an experimental study to find out whether there is any learning achievement of students who are taught writing descriptive text using photographs as media which is significantly different from those who are taught without photographs. The subjects of the study were the 8th year students of SMP Negeri 1 Ungaran. In order to achieve the objective, the researcher conducted an experimental research. There were two groups involved in this research, the experimental and the control group. The experimental group was taught using photographs in Instagram and the control group was taught without using photographs in Instagram. After both groups were given the treatment, the result of the study shows that the mean score of experimental group was 74.80 and the control group was 72.63. It means that the score of the experimental group was higher than the score of the control group. The t-test result showed that t-value was 2.056 and t-table was 2.002, which means that the t-value is higher than the t-table. It proves that there is a significant different achievement between the groups which taught using photographs in Instagram and using conventional teaching. Based on the result of this study, it is concluded the application of photographs in Instagram can improve students’ writing skill in writing descriptive text. It was effective and recommended for the English teacher as one of references in teaching and learning process.